As processadoras de fertilizantes em Catalão (GO): do consumo produtivo do agronegócio à produção do espaço urbano - (:unkn) unknown (Universidade Federal de Goiás, 2020)
The industrialization process in the municipality of Catalão, starts from the 1970s in line with the Goian and national context. The first industries that installed in the municipality werw mining companies, (Metago) in 1968, (Goiasfertil) in 1975 and (Mineração Catalão) in 1976, howevwe, this process has intensified since 1990 with the industrial economic decentralization of state legislation and industrializatin incentives taking to migration of various industries to the Centro-Oeste, is involved in this process that Catalão received several companies from vehicle manufactorers, of harvesters, and their respective subsidiaries. The investments in the verticalization the chemical processing of phosphatesand on the part two (current CopeBras and Mosaic) and the national growth of agricultural production made it possible to attraction of fertilizer industries, mainly post 2002. These are the factors that justify the problem the presente research, to which we seek answers to the following question: What conditions and aspects influenced the attraction of the processing industries of fertilizers in Catalão (GO)?. And that sustain the general objective of this research what is: Understand the factors that induced installation of fertilizer processing industries in Catalão/Goiás, through the organization of productive circuits that articulares the space on multiple scales and with effects on dynamics local urban. The procedures methodological, are based on research theoretical that adresses the importance of the industrial process, of consumption productive agricultural, of the circuits of the economy urban, the role of the processing industries of fertilizers in production and reproduction of urban space in Catalão. The main concepts used are: urban space, industrialization, consumption productive, and the two circuits of the urban economy, sustained by theorists how: Santos (1979), Corrêa (1989), Elias (2003), among others. For documentar research we use data from IBGE (2015, 2018), IMB (2015,2019) and others to analyse the process of urban expansion and economic development. Finally, visits of field that werw based on observation and photographic record of fertilizer industries (without nominal identification) and some commercial establishments linked to the productive consumption of agribusiness. Therefore, per hour, this study it is important to understand better production of space in Catalão, once, that in that same space are distributed some productive segments important for the economy.
Fertilizer processors in catalão (GO): from the productive consumption of agribusiness to the production of urban space
Keywords: Espaço urbano; Consumo produtivo; Circuitos da economia urbana; Indústria de fertilizantes; Urban space; Proctive consumption; Urban economy circuits; Fertilizer industries; Catalão (GO); Catalão (GO); CIENCIAS HUMANAS::GEOGRAFIA